4-HNE Adduct Stability Characterized by Collision-Induced Dissociation and Electron Transfer Dissociation Mass Spectrometry - Fritz, Kristofer S. (2012)
4-hydroxynonenal (4-HNE) alters numerous proteomic and genomic processes. Understanding chemical mechanisms of 4-HNE interactions with biomolecules and their respective stabilities may lead to new discoveries in biomarkers for numerous diseases of oxidative stress. Collision-induced dissociation (CID) and electron transfer dissociation (ETD) MS/MS were utilized to examine the stability of a 4-HNE-Cys Michael adduct. CID conditions resulted in the neutral loss of 4-HNE, also known as a retro-Michael addition reaction (RMA). Consequently, performing ETD fragmentation on this same adduct did not result in RMA. Interestingly, 4-HNE adduct reduction via sodium borohydride (NaBH(4)) treatment stabilized against the CID induced RMA. In a direct comparison of three forms of 4-HNE adducts, computational modeling revealed sizeable shifts in the shape and orientation of the lowest unoccupied molecular orbital (LUMO) density around the 4-HNE-Cys moiety. These findings demonstrate that ETD MS/MS analysis can be used to improve the detection of 4-HNE-protein modifications by preventing RMA reactions from occurring.